Implementasi Dukungan Ambulasi pada Ny.E Post Sectio Caesarea dengan Intoleransi Aktivitas di Ruang Gincu 4 RSUD Indramayu - Nengsih Yulianingsih; Alayshah Alayshah (Universitas Muhamadiyah Manado, 2024)
Background: In clients post Sectio Caesaria (SC), many problems arise, including anxiety. The reason for anxiety in mothers post Sectio Caesaria (SC) is because they don't know how to care for post partum including post Sectio Caesaria (SC) wound care, breast care, exclusive breastfeeding, giving nutrition to babies, caring for newborns and anxiety because they are afraid of the stitches coming out. , afraid of infection in the wound. From this problem, activity intolerance nursing problems will arise where the client is unable to carry out daily activities independently and abnormal vital signs are found during or after activities. Early mobilization exercises are useful for improving blood circulation, preventing thromboembolism, surgical muscle stiffness, stimulates gastrointestinal function and reduces pain. The aim is to explore nursing care for clients with acute pain problems in post SC clients. The aim is to explore nursing care for clients with acute pain problems in post SC clients. The data collection method used in this case study is descriptive, namely interviews, observation and physical examination, documentation studies and collecting results from diagnostic examinations. The results of this nursing care show that after implementing ambulation support for 3 days, the patient began to improve from being previously still lying in bed to now being able to move and be active again, the ease of carrying out daily activities increased. Walking distance increases, lower body strength increases, dyspnea during activity decreases, dyspnea after activity decreases, oxygen saturation improves, respiratory frequency improves. It was concluded that from the results of this case study over 3 visits, the problem could be resolved by teaching clients to carry out physical mobilization techniques aimed at increasing their ability to do activities. Advice for clients is that clients can maintain their physical condition.